2010
DOI: 10.3389/fnsyn.2010.00026
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation provides means to assess cortical plasticity and excitability in humans with fragile X syndrome and autism spectrum disorder

Abstract: Fragile X Syndrome (FXS) is the most common heritable cause of intellectual disability. In vitro electrophysiologic data from mouse models of FXS suggest that loss of fragile X mental retardation protein affects intracortical excitability and synaptic plasticity. Specifically, the cortex appears hyperexcitable, and use-dependent long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength are abnormal. Though animal models provide important information, FXS and other neurodevelopmental diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 57 publications
4
75
0
Order By: Relevance
“…Specifically, and consistent with our previous studies (Oberman et al , 2012, compared with the control group on day 1, the ASD group showed a significantly greater duration of response to cTBS, whereas the FXS group showed a significantly shorter duration (on average no discernable response). Our results confirm and extend those findings.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Specifically, and consistent with our previous studies (Oberman et al , 2012, compared with the control group on day 1, the ASD group showed a significantly greater duration of response to cTBS, whereas the FXS group showed a significantly shorter duration (on average no discernable response). Our results confirm and extend those findings.…”
Section: Discussionsupporting
confidence: 90%
“…cTBS was applied according to the standard protocol that was consistent with our previous studies in ASD and FXS (i.e., three pulses of 50-Hz rTMS repeated every 200 ms for a total of 40 seconds [for a total of 600 pulses]) at an intensity of 80% of AMT (Huang et al 2005(Huang et al , 2008Oberman et al 2010Oberman et al , 2012Oberman et al , 2015. Corticospinal excitability was assessed both before and after cTBS by measuring peak-to-peak amplitude of MEPs induced in the contralateral first dorsal interosseus (FDI) muscle in response to supra threshold (120% of resting motor threshold [RMT] intensity) single-pulse TMS.…”
Section: Stimulation and Recordingmentioning
confidence: 99%
See 3 more Smart Citations